(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2024)
Over the course of its history, India’s labour laws have undergone significant change in an attempt to achieve a balance between the advancement of the economy and the protection of workers’ rights. Nevertheless, a significant concern is the potential impact that these restrictions may have on working women in particular. There are various challenges that women face in India’s official and informal workforces, and this article examines the scope, effectiveness, and limitations of the laws that are in place to address these challenges. Certain essential regulations, such as those that protect women and their children from wage theft, equal pay for equal labour, prohibitions against sexual harassment in the workplace, and the new labour standards, are examined from a gendered perspective in this article. The findings of the research indicate that there are continuous implementation gaps, particularly in the unorganised sector, which is where the majority of women are employed. The structural issues that are addressed include, but are not limited to, unpaid care work, unsafe working conditions, an imbalance in wages between men and women, and a lack of social security. Using policy papers, legal studies, and implementation reports, this essay draws attention to the need of enhancing enforcement mechanisms and implementing labour reforms that are sensitive to gender issues. Even though there are legal safeguards in place, it is evident from the findings that women in India’s employment need a more inclusive approach to labour policy in order to be empowered and protected. This is the case even if their rights are guaranteed by law.